Factors driving IPO variability: evidence from Pakistan stock exchange. Issue 52 (23rd August 2021) - Mehmood, Waqas; Mohd-Rashid, Rasidah; Ong, Chui Zi; Abbas, Yasir Abdullah
Abstract : Purpose: The objectives of this study are twofold. First, it intends to investigate the symmetric link between initial public offering (IPO) variability and the determinants of the stock market index, treasury bill rate, inflation, GDP growth rate and foreign direct investment. Second, this study intends to examine the asymmetric link between IPO variability and the aforementioned determinants, namely the stock market index, treasury bill rate, inflation, GDP growth rate and foreign direct investment. Design/methodology/approach: Data from 1992 to 2018 were gathered from the country of Pakistan in order to achieve the above objectives. Augmented Dickey–Fuller (ADF) and Phillips Perron (PP) unit root tests were employed to determine the data's stationarity properties. The Auto Regressive Distributive Lags (ARDL) model was utilized to examine the symmetric links, and the Non-Linear Auto Regressive Distributive Lag Model (NARDL) was employed to determine the asymmetric links. While the long-run co-integration was examined using the ARDL bound test, the short-run dynamics were tested using the error correction method (ECM). Findings: The macroeconomic variables of the stock market index, treasury bill rate, inflation, GDP growth rate and foreign direct investment are found to pose significant short-run and long-run symmetric and asymmetric effects on IPO variability. These results indicate the significance of the aforementioned variables in enhancing IPO variability. The findings also demonstrate the typical reactions of inflation, GDP and FDI towards negative and positive shocks in IPO variability and inflation. This evidence implies that Pakistan's poor capital market development is reflected in the country's weak macroeconomic factors. At the same time, the reduced IPO variability in the country also reflects the lack of confidence among prospective issuers and investors due to Pakistan's weak macroeconomic indicators. Originality/value: This is the first study of its kind to properly investigate the symmetric and asymmetric effects of the macroeconomic variables on Pakistan's IPO variability.